Studi pengaruh kadar mangan dan temperatur austenisasi terhadap struktur mikro dan sifat mekanik baja mangan - Bahfie, Fathan; Aleiya, Zakhrofa; Milandia, Anistasia; Nurjaman, Fajar (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
High manganese steel or austenitic manganese steelcommonly are used in mining industries such as thecomponent in an excavator, hammer mill, crusher, andjaw crusher plates. Those components are the alloy caststeel with containing manganese (Mn) about 11-18%.The mechanical properties of austenitic manganesesteel are depending on the amount of manganese andcarbon. The austenitic steel has three dominantproperties, i.e. high hardness; good wear resistance, andhigh impact resistance. The objectives of this researchare investigating the effect of the composition ofmanganese and the austenitization temperature on themicrostructure and mechanical properties of austeniticmanganese steel. Each variation of manganesecomposition was 5.87%. 9.42% and 15.28%. It washeated at 950, 1000 and 1050oC for 60 minutes and thenquenched with water. The result showed that the highesthardness was 46 HRC where the composition ofmanganese and the austenitization temperature was5.87%. and 1050oC. The lowest hardness number was16.3 HRC where the content of manganese and thetemperature was 9.42%. and 1050oC. The results agreedwith the microstructure of the increase in carbides andthe composition of manganese increased too. For thewear resistance properties, the optimum one was 6.78 x10-6 mm3/m at the composition of manganese andtemperature of 5.87% and 1050oC.